Fated - Zanetti, Rebecca (Zanetti, Rebecca. Dark protector series, 2011)
"Cara Paulsen does not give up easily. A scientist and a single mother, she's used to fighting for what she wants, keeping a cool head, and doing whatever it takes to protect her daughter Janie. But 'whatever it takes' has never before included a shotgun wedding to a dangerous-looking stranger with an attitude problem. Sure, the mysterious Talen says that he's there to protect Cara and Janie. He also says he's a three-hundred-year-old vampire..."--P. [4] of cover.